Integrating human perceptions into ecological restoration: Analyzing the mismatches and barriers between ecological components, ecosystem services, and human perceptions in riparian green spaces - Ce Wen; Fan Yang; Xing Zhang; Hongda Fang; Yuanpeng Fu; Xuxi Zhou; Changzhou Yan (Ecological Engineering, 2026)

Selective cleavage of Cβ-O-containing Cα-Cβ bond on Cu-Ni3S2 for electrocatalytic glycerol oxidation to formic acid - Ruirui Xu; Xinti Yu; Ce Fu; Lina Li; Zhangxing Chen; Heng Zhao (Chemical Engineering Journal, 2026)

40Ar/39Ar geochronology, SrNd isotopes and melting conditions of the Dahongshan alkaline basalts: Constraints on mantle modification beneath the northern Yangtze Craton - Yue Song; Xuan-Ce Wang; Simon A. Wilde; Xiang-Zhong Li; Chong-Jin Pang; Si-Yu Hu; Yang Luo; Jia-Xu Tang; Si-Zhe Fu (Chemical Geology, 2026)

Zedoarondiol inhibits monocyte adhesion and expression of VCAM and ICAM in endothelial cells induced by oxidative stress - Bei-li Xie; Yu-long Bie; Bo-ce Song; Ming-wang Liu; Lin Yang; Jiangang Liu; Da-Zhuo Shi; Fu-Hai Zhao (Natural Product Research, 2026)

Flexible fluorescent sensor based on a heterojunction-functionalized hydrogel with dual-mode crosslinking for H2S monitoring during fish spoilage - Zhixin Jia; Jingbin Zhang; Haocheng Fu; Zengtao Ji; Jiaran Zhang; Xinting Yang; Ce Shi; Xia Sun; Yemin Guo (Chemical Engineering Journal, 2025)

Cardiomyocyte regeneration after infarction: changes, opportunities and challenges - Ce Cao; Lili Yang; Jianshu Song; Zixin Liu; Haoran Li; Lei Li; Jianhua Fu; Jianxun Liu (Molecular and Cellular Biochemistry, 2025)

3D adaptive finite-element forward modeling for direct current resistivity method using geometric multigrid solver - Ce Qin; Wenliang Fu; Ning Zhao; Jun Zhou (Computers & Geosciences, 2025)

Control of stepwise subduction and slab breakoff on volcanism and uplift in the Tibetan Plateau - Jian Wang; Zhi Wang; Xiugen Fu; Xuan-Ce Wang; Simon A. Wilde; Yi Fu; Jian Lin; Hengye Wei; Lijun Shen; Gang Rao; Ahmed Mansour (Earth and Planetary Science Letters, 2024)

Multi-dimensional microfluidic paper-based analytical devices (μPADs) for noninvasive testing: A review of structural design and applications - Ting Chen; Ce Sun; Syed Comail Abbas; Nur Alam; Sheng Qiang; Xiuzhi Tian; Chenglong Fu; Hui Zhang; Yuanyuan Xia; Liu Liu; Yonghao Ni; Xue Jiang (Analytica Chimica Acta, 2024)

A novel detection method for sulfur content in ship fuel based on metal-doped tin oxide quantum dots as fluorescent sensor - Jianqiao Liu; Wenping Li; Hongjin Li; Yanan Zhang; Zhaoxia Zhai; Yang Wang; Ce Fu; Junsheng Wang (Fuel, 2024)

Anti-freeze hydrogel-based sensors for intelligent wearable human-machine interaction - Zhiwei Fu; He Liu; Qingying Lyu; Jingwei Dai; Ce Ji; Ye Tian (Chemical Engineering Journal, 2024)

Establishment of CRISPR-Cas-based antiparasitic agents for the swimming crab parasite Mesanophrys sp. - Xiaopeng Wang; Yueyue Zhou; Yingchao Zhang; Xiaofen Song; Ce Shi; Yuanyuan Fu; Lei Liu; Changkao Mu; Fei Yin; Weiwei Song; Chunlin Wang (Aquaculture, 2024)

Efficient synthesis of PdIr nanocatalysts with controllable surface composition for electrochemical oxidation of methanol - Ce Fu; Pan Wang; Rong-Hua Zhang; Luo-Yi Yan; Zheng Cheng; Xin Zhang; Xin-Wen Zhou (Fuel, 2023)

Selective NO2 Detection by Black Phosphorus Gas Sensor Prepared via Aqueous Route for Ship Pollutant Monitoring - Yang Wang; Yujia Wang; Yue Sun; Kuanguang Zhang; Chenyang Zhang; Jianqiao Liu; Ce Fu; Junsheng Wang (Journal of Marine Science and Engineering, 2022)
The emission of nitrogen dioxide (NO2) caused by marine transportation has attracted worldwide environmental concerns. Two-dimensional (2D) black phosphorus (BP) is an emerging semiconductive material with the advantages of high electron mobility, a layer-dependent direct band gap and a large specific surface area. These properties ensure excellent potential in gas-sensing applications. In this work, BP quantum dots (QDs) are synthesized from commercial red phosphorus (RP) fine powder via the aqueous route. The BP QDs show uniform size distribution with an average size of 2.2 nm. They are employed to fabricate thin film gas sensors by aerial-assisted chemical vapor deposition. The microstructure, morphology and chemical composition are determined by various characterizations. The sensor performances are evaluated with the optimized response set to 100 ppm NO2 of 10.19 and a sensitivity of 0.48 is obtained. The gas sensor also demonstrates excellent repeatability, selectivity and stability. The fabricated thin film gas sensor assembled by BP QDs exhibits prospective applications in selective NO2 detection for marine gaseous pollutant monitoring and control.

Spatiotemporal Distribution of Asian Horseshoe Crab Eggs Are Highly Intermingled with Anthropogenic Structures in Northern Beibu Gulf, China - Kit Yue Kwan; Yijian Fu; Mufeng Zhong; Yang Kuang; Haiwei Bai; Ce Zhang; Wenquan Zhen; Peng Xu; Chun-Chieh Wang; Junhua Zhu (Journal of Ocean University of China, 2022)

An integrated assessment of INDCs under Shared Socioeconomic Pathways: an implementation of C3IAM - Yi-Ming Wei; Rong Han; Qiao-Mei Liang; Bi-Ying Yu; Yun-Fei Yao; Mei-Mei Xue; Kun Zhang; Li-Jing Liu; Juan Peng; Pu Yang; Zhi-Fu Mi; Yun-Fei Du; et al. (Natural Hazards, 2018)

Development of rRNA-targeted probes for detection of Prorocentrum micans (Dinophyceae) using whole cell in situ hybridization - Guo Fu Chen; Yang Liu; Chun Yun Zhang; Chao Shuai Ma; Bao Yu Zhang; Guang Ce Wang; Zhong Xu; Dou Ding Lu (Journal of Applied Phycology, 2013)

Inducible expression of human angiostatin by AOXI promoter in P. pastoris using high-density cell culture - Ai-Lian Zhang; Tian-Yuan Zhang; Jin-Xian Luo; Ce-Yi Fu; Zhi Qu; Guo-Hui Yi; Dong-Xiao Su; Fa-Zhi Tu; Ying-Wen Pan (Molecular Biology Reports, 2009)

Recent advances on the GAP promoter derived expression system of Pichia pastoris - Ai-Lian Zhang; Jin-Xian Luo; Tian-Yuan Zhang; Ying-Wen Pan; Yan-Hua Tan; Ce-Yi Fu; Fa-zhi Tu (Molecular Biology Reports, 2009)